METHODOLOGY FOR IDENTIFYING OPERATING OBJECTS IN OIL FIELD DEVELOPMENT BASED ON MATHEMATICAL AND STATISTICAL INDICATORS (USING THE EXAMPLE OF THE PIRALLAHI (NORTHERN FOLD) FIELD) - SULEYMANOVA, Vafa; MANSUROVA, Samira; MAMMADOVA, Nazile (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. In this research, a table based on samples taken from wells in each of the two horizons and using the formation parameter values was compiled. As a result of the researches, five formation parameters (geological and technological) were included in the matrix, and parametric criteria were used to determine the degree of similarity or difference between the upper and lower layers of the KS. Methods. In Pirallahi using the actual data of the wells that opened both layers, (CUS and CLS) calculations were made according to statistical indicators based on the values of the relevant indicators and checked with parametric criteria. Since the calculated prices are lower than the table values and there is a similarity between both objects, it is recommended to combine them and operate them together. Such an approach leads to intensification of development. Results. Due to the examination of complex geological and operational data, the following proposals are recommended along with the consolidation of similar layers in the north of Pirallahi. Conclusions. Thus, since the geological and production indicators between the objects KSupper and KSlower are almost similar, it is advisable to combine them into one object and exploit one grid of wells. The allocation of such objects leads to the intensification of exploitation, and the results can be used in drawing up projects for the development of such layers.